2011
DOI: 10.1016/j.eswa.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive approach to enhanced traffic signal optimization by using soft-computing techniques

Abstract: This paper presents an application of diverse soft-computing techniques to adaptive traffic light controls. The proposed methodology consists of two main phases: off-line and on-line. First, clustering techniques and optimization methods are used at the off-line stage to discover the prototypes which characterize the traffic mobility patterns at an intersection. After this process an optimum timing plan is decided for each mobility pattern detected. In the on-line phase, a prediction model is then constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This scheme is based on CTDP and employs the classical structure proposed in the literature based on two phases, off-line and on-line (see Antoniou et al, 2011). The essential ideas of the proposed approach were suggested in Angulo et al (2011). This prototype of urban traffic control system is based on clustering/classification techniques.…”
Section: A Prototype Of An Urban Traffic Control System For Small Andmentioning
confidence: 99%
“…This scheme is based on CTDP and employs the classical structure proposed in the literature based on two phases, off-line and on-line (see Antoniou et al, 2011). The essential ideas of the proposed approach were suggested in Angulo et al (2011). This prototype of urban traffic control system is based on clustering/classification techniques.…”
Section: A Prototype Of An Urban Traffic Control System For Small Andmentioning
confidence: 99%
“…In contrast, signal timing plans at https://doi.org/10.36909/jer.v8i4.8349 isolated intersections operate independently, and these intersections do not have any connection. Isolated signal timing systems are summarized in two main categories: nonadaptive and adaptive signal control systems (Angulo et al, 2011). Nonadaptive traffic signal control corresponds to fixed-time signal control systems, and adaptive traffic signal control systems apply signal timing plans according to changes in the traffic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Nonadaptive traffic signal control corresponds to fixed-time signal control systems, and adaptive traffic signal control systems apply signal timing plans according to changes in the traffic flow. Since real-time monitoring of traffic conditions with developing technology allows reaching the instant real-world data, it would be easier to manage the traffic with adaptive signal control approaches (Angulo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Obtained results showed that realtime adaptive management model is quite successful for improving the performance of intersection. Angulo et al [17] presented an application of different computing techniques for adaptive traffic management. e model developed was compared with nonadaptive static and dynamic management.…”
Section: Introductionmentioning
confidence: 99%